2009
DOI: 10.1016/j.brs.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment by electrical stimulation of the auditory cortex for intractable tinnitus

Abstract: Tinnitus is a public health issue in France. Around 1% of the population is affected and 30,000 people are handicapped in their daily life. The treatments available for disabling tinnitus have until now been disappointing. We are reporting on the surgical treatment by electrical stimulation of the auditory cortex of a female patient affected by disabling tinnitus that resisted classical treatments. The tinnitus appeared suddenly 10 years ago after a left ear tympanoplasty. The acouphenometry measures revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…This approach has been replicated by other centers. A French study obtained long-lasting 65% tinnitus reduction in a woman using a fMRI based extradural auditory cortex implant (Litre et al, 2009, 2010). Another study of eight patients using a similar technique but different hardware found no permanent tinnitus suppression (Friedland et al, 2007).…”
Section: The Involvement Of Central Auditory Pathways In Tinnitusmentioning
confidence: 99%
“…This approach has been replicated by other centers. A French study obtained long-lasting 65% tinnitus reduction in a woman using a fMRI based extradural auditory cortex implant (Litre et al, 2009, 2010). Another study of eight patients using a similar technique but different hardware found no permanent tinnitus suppression (Friedland et al, 2007).…”
Section: The Involvement Of Central Auditory Pathways In Tinnitusmentioning
confidence: 99%
“…Pour notre part, nous nous sommes basés sur des travaux réalisés sur la rTMS du cortex auditif secondaire de schizophrènes présen-tant des hallucinations auditives (Hoffman et al, 2003). Positionner l'électrode plus en arrière semble permettre une double action sur la réduction de l'acouphène : direct par le cortex auditif, et indirect sur le ressenti par les aires associatives hétéromodales (Litre et al, 2009). Enfin, il paraît admis actuellement que le positionnement de l'électrode doit être controlatéral à l'acouphène (Eichhammer et al, 2003).…”
Section: Discussionunclassified
“…Au deuxième jour postopératoire, nous avons mis en route le stimulateur, en adoptant des paramètres de stimulation proposés dans la littérature existante (Nguyen et al, 2000 ;Nguyen et al, 1999 ;De Ridder et al, 2006 ;Litre et al, 2009).…”
Section: Suivi Et Réglage Du Stimulateurunclassified
“…Tinnitus is a prevalent symptom, with clinical, pathophysiological, and treatment features analogous to pain. Invasive auditory cortex stimulation (iACS) via implanted electrodes onto or into the primary auditory cortex (inside the posterior part of the Sylvian valley) or overlying the secondary auditory cortex (posterior part of the superior temporal gyrus) have been developed to treat severe cases of intractable tinnitus (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)50).…”
Section: Auditory Cortex Stimulation For Tinnitusmentioning
confidence: 99%
“…The same holds for tinnitus. Whereas in most studies the electrodes are implanted extradurally or intradurally overlying the primary or secondary auditory cortex respectively (16)(17)(18)(19)(20)(21)(22)(23)(24), some patients have been treated with wire electrodes implanted inside the auditory cortex (25). We will consider any form of cortical stimulation, whether intracortical or onto the cortex, as cortical stimulation, and deep brain stimulation as specifically targeting deep nuclei, rather than cortical structures.…”
Section: Introductionmentioning
confidence: 99%